Using of DDU Temperature Models for Predicting the Spread of Dirofilariosis in Dogs in Various Regions of the Republic of Armenia - R. V. Slobodyanik; S. S. Zykova; A. L. Kryazhev (Российский паразитологический журнал, 2020)
The purpose of the research is to study the possibility of using the temperature DDU (dirofilaria development units) model for predicting the spread of dirofilariosis in dogs in various regions of the Republic of Armenia.Materials and methods. To obtain temperature models of dirofilariosis in various regions of Armenia, the method of mathematical modeling was applied. The method for determining the number of generations of Dirofilaria spp. infection is based on the effect of the average daily air temperature on the rate of development of Dirofilaria larvae in mosquitoes with a threshold of 14 °C. For a negative value of DDU, the value is set to zero. At temperatures above the threshold, DDU accumulate. For the development of larvae to the infective stage, an amount of 130 DDU is required. The number of possible generations of one generation of larvae L3 was calculated by dividing the annual sum of temperatures above 14 °C by 130 DDU, taking into account that 130 DDU should accumulate within a period not exceeding 30 days. The calculation uses daily data on the average daily air temperature in the period from 2017 to 2019 for Shirak, Aragatston, Armavir and Ararat regions of Armenia.Results and discussion. Temperature modeling of DDU is not of high significance, since it takes into account only the average daily air temperature and does not take into account other factors affecting the incidence rates. The largest number of generations of larvae in mosquitoes could be realized in the Armavir and Ararat regions – on average, 16 generations per year. At the same time, the infection of dogs with dirofilariae in the Armavir region was 42.8%, and in the Ararat region – 29.6%. In Aragatston region, on average, 14–15 generations are developing per year. Dirofilariosis was not detected in the studied dogs. In the Shirak region, on average, 7–8 generations are developing per year. Dirofilariae infection was detected in 3.6% of the dogs studied. Based on the temperature DDU-model of dirofilariosis (on the dates of the end of the first and last incubation of dirofilariosis larvae in mosquitoes for several years), as well as the results of phenological observations, we have developed schemes for effective prevention of dirofilariosis. In order to organize and conduct veterinary preventive measures to prevent infestation of dogs by dirofilariae, it is necessary to organize two lines of defense. The first line of defense: the use of anthelmintics from the group of macrocyclic lactones in Aragatston, Armavir and Ararat regions, which is carried out monthly, and in the Shirak region - from April to January. The second line of defense is repellant treatment of dogs in the Aragatston, Armavir and Ararat regions from March to November, and in the Shirak region from April to October. The practical application of temperature DDU-models of dirofilariosis allows specialists of veterinary and sanitary services to establish the timing of the epizootic season of dirofilariosis, as well as organize and conduct veterinary preventive and therapeutic measures among the population of dogs in endemically disadvantaged areas of the republic.